Assessment of mobile screen time, sleep quality, and reaction time in young adults with premenstrual dysphoric disorder - Doreswamy Kanakaiah; Varun Manjunath; Venkatesha R; Yashica Gowda R; Sai Sailesh Kumar Goothy; Sadgunothama Goud Kamparaj; Anitha Lakshmi (Asian Journal of Medical Sciences, 2025)
Background: Premenstrual syndrome is observed in the late luteal phase of the menstrual cycle. However, the studies related to the assessment of screen time, sleep quality, and reaction time (RT), in young adults with premenstrual dysphoric disorder are sparse in the Indian scenario. Hence, the present study was undertaken. Aims and Objectives: The present study was undertaken to observe the assessment of screen time, sleep quality, and RT in young adults with premenstrual dysphoric disorder (PMDD). Materials and Methods: A total of 1200 participants were screened and 150 participants were recruited for the study. Willing females within the age group of 18–24 with positive responses to five or more of 11 Diagnostic and Statistical Manual of Mental Disorders-5 criteria were part of the study. A total of 150 willing, age-matched controls were also part of the study. Mobile screen time was recorded using Your Hour app. Sleep quality was assessed using an insomnia severity index questionnaire. Auditory and visual RT (VRT) was recorded using the RT apparatus. Results: Significantly higher screen time and significantly higher insomnia scores were observed in the participants with PMDD. Both the auditory and VRT were significantly longer in the PMDD cases when compared with healthy individuals. Conclusion: The study results support that longer screen time is associated with PMDD as it affects sleep adversely. Further, the RT is longer in PMDD cases than in healthy controls. Hence, reducing screen time may help as a simple remedy along with the regular management of PMDD.